Humanist Translation and the Parisian Tradition : Jacques Lefèvre d'Étaples's ps.-Dionysius the Areopagite - Lundberg, Christa ; 0000-0002-5333-2995 (Journal of the History of Ideas, 2025)
Responding to recent studies on the reception of Church Fathers, this paper contributes a study of how Jacques Lefèvre d'Étaples edited the writings of ps.-Dionysius the Areopagite in Latin. Focusing on how Lefèvre revised the Latin translation by Ambrogio Traversari (1386-1439), I argue that Lefèvre adapted Traversari's text to a new context by aligning the translation with earlier Latin renderings. The article thereby undermines earlier assumptions about Lefèvre's engagement with Greek manuscripts, demonstrates continuities in the use of Latin translations of Greek patristics before and after printing, and highlights the cultural dimension of the editor's craft.
Keywords: Pseudo-Dionysius the Areopagite; Lefèvre d’Étaples; Ambrogio Traversar; Editing; Translating; French Humanism; John Scotus Eriugena